Analysis of Micropolar and Power Law Fluid–Lubricated Slider and Journal Bearing with Partial Slip–Partial Slip Texture Configuration. Issue 5 (2nd September 2016) - Rao, T. V. V. L. N.; Rani, A. M. A.; Nagarajan, T.; Hashim, F. M.
ABSTRACT: An analysis of micropolar and power law fluid–lubricated partial slip–partial slip texture slider and journal bearings is presented. The nondimensional pressure and shear stress expressions for a partial slip texture configuration are analyzed using narrow groove theory. The parameters used in the analysis are nondimensional partial slip length, nondimensional partial slip–partial slip texture length, nondimensional depth of recess, ratio of land with slip to recess, nondimensional slip coefficient, coupling number; ratio of characteristic length to film gap, and power law index. A partial slip configuration with a higher slip coefficient yields an improvement in load capacity and reduction in coefficient of friction compared to a partial slip texture configuration for micropolar and power law shear thinning (pseudoplastic) fluid-lubricated slider and journal bearings.